Analysis of the factors influencing the effectiveness of local government’s purchase of older adults care services – a grounded theory study based on typical cases - Liu, Sujun (Frontiers in Public Health, 2023)
Background: Population ageing is a basic national condition in China at present and for a long time to come, forcing the country to accelerate the pace of building its public older adults care system. The government's purchase of older adults care services has become an effective way to make up for the lack of the family's older adults care function, to which the Chinese government attaches particular importance. The article selects 11 typical cases from the excellent case base released by the Chinese Ministry of Civil Affairs officials in 2022 to study the influencing factors of the effect of local government purchase of older adults care service supply. Methods: NVivo data analysis tools have significant advantages in retrieving, analyzing and coding data more efficiently and accurately, which helps to construct theoretical propositions and formulate hypotheses to be tested in qualitative research. The study intends to adopt the grounded theory approach to analyze the text with the help of NVivo12 software, to condense the practice mechanism of local governments' purchasing of older adults care services and to construct a relational model. Results: Taking "the supply effect of local government purchasing older adults services" as the main logic line, the article summarizes the four main influencing factors of the supply effect of government purchasing older adults services: the real demand of the society, the government's power and responsibility system, the government's governance ability, and the society's acceptance ability. Conclusion: The sense of gain, happiness and security of the older adults group is the starting point and landing point of the older adults service policy formulation and implementation. Policy guidance and decision-making have an important impact on the quality of the supply of older adults care services and the development of the older adults care services industry. Clarifying the direction of policy guidance, reflecting the comprehensive efficiency of government governance and utilizing the professional advantages of social forces, is the key to improving the effectiveness of the government's purchase of older adults care services.